ANALISIS PENINGKATAN KINERJA PEMERINTAH DESA PADA DESA DI KABUPATEN MERANTI - Vera oktari; Ulfa Afifah; Arumega Zarefar; Mayla Khoiriyah (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2021)
In improving its performance, the village government requires to have organizational commitment that supported by apparatus competency and controlled through community participation. The purpose of this study was to examine the effect of organizational commitment, community participation, and apparatus competence on village government performance. 200 data collected from questionnaires will be analyzed to identify organizational commitment, community participation, and apparatus competency towards the village government performance. Data analyzed by using SPPS version 25.0. the result of data processing found that organizational commitment, community participation, and apparatus competency affects the village government performance, and the organizational commitment is needed to improve apparatus competency by educating and training its human resources, also the transparency as the form of responsibility of the village government to citizen